Counselling Human Beings of the Female Sex - Delehanty, Rosalyn (Canadian Journal of Counselling and Psychotherapy, 2012)
Two questions are considered: (1) whether women experience sex discrimination in counselling and (2) whether an adequate solution to experienced sex bias is counselling by the same sex counsellor. Relevant literature is cited, and it is concluded (1) that although there is evidence of sexist bias in counselling and in definitions of "mental health," there is little evidence that male counsellors arc more subject to bias than female counsellors; and (2) that it is essential for both male and female counsellors to be aware of how their social values and sexual biases may affect their attitudes and behaviour toward clients of either sex; and (3) that bias brought to counselling by clients must be considered a significant factor in the determination of counsellor credibility.